A novel symmetrically multifunctionalized dodecamethoxy-cycloparaphenylene: synthesis, photophysical, and supramolecular properties. Issue 9 (13th March 2018) - Lu, Dapeng; Zhuang, Guilin; Jia, Hongxing; Wang, Jinyi; Huang, Qiang; Cui, Shengsheng; Du, Pingwu
Abstract : In the present study, we report the synthesis of a novel symmetrically multifunctionalized cycloparaphenylene (CPP), dodecamethoxy-[9]CPP, through nickel-mediated macrocyclization and subsequent reductive aromatization reactions. Abstract : In the present study, we report the synthesis of a novel symmetrically multifunctionalized cycloparaphenylene (CPP), dodecamethoxy-[9]CPP (ring[9]arene), through nickel-mediated macrocyclization and subsequent reductive aromatization reactions. The electron-donating methoxy groups were introduced onto the curved precursor at an early stage to avoid the problem of non-selective functionalization of CPPs. Compared to [9]CPP, the present dodecamethoxy-[9]CPP shows a significant red shift (>73 nm) in the fluorescence spectrum. In addition, theoretical calculations revealed its increased torsion angles and ring strain (71.01 kcal mol −1 ) compared with its unsubstituted counterpart.